2010
DOI: 10.1074/jbc.m109.062877
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-10b Promotes Migration and Invasion through KLF4 in Human Esophageal Cancer Cell Lines

Abstract: Recently, microRNAs have emerged as regulators of cancer metastasis through acting on multiple signaling pathways involved in metastasis. In this study, we have analyzed the level of miR-10b and cell motility and invasiveness in several human esophageal squamous cell carcinoma cell lines. Our results reveal a significant correlation of miR-10b level with cell motility and invasiveness. Overexpression of miR-10b in KYSE140 cells increased cell motility and invasiveness, whereas inhibition of miR-10b in EC9706 c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
207
2
7

Year Published

2010
2010
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 275 publications
(228 citation statements)
references
References 51 publications
11
207
2
7
Order By: Relevance
“…Several other studies subsequently found increased expression of miR-10b to be associated with aggressive behavior in various cancers. [34][35][36][37][38] In melanoma, miR-10b was identified in miRNA discovery studies 9,39 but no studies have focused on miR-10b as the primary melanoma candidate biomarker. Segura et al 9 conducted a discovery analysis in melanoma and miR-10b was associated with increased post-recurrence survival, which contradicts our findings.…”
Section: Discussionmentioning
confidence: 99%
“…Several other studies subsequently found increased expression of miR-10b to be associated with aggressive behavior in various cancers. [34][35][36][37][38] In melanoma, miR-10b was identified in miRNA discovery studies 9,39 but no studies have focused on miR-10b as the primary melanoma candidate biomarker. Segura et al 9 conducted a discovery analysis in melanoma and miR-10b was associated with increased post-recurrence survival, which contradicts our findings.…”
Section: Discussionmentioning
confidence: 99%
“…MIR10B has been implicated in the past in multiple cancers, including in head and neck (58)(59)(60)(61)(62). Unlike in some cancers, its role in HNSCC is unclear (63).…”
Section: Discussionmentioning
confidence: 99%
“…Western Blot Analysis-Western blots were performed as described previously (25). Antibodies used were anti-p53 (Sc-126, Santa Cruz Biotechnology, Santa Cruz, CA), anti-S100A14 (gifts of Dr. Iver Petersen, University Hospital Charité, Berlin, Germany, and Dr. Youyong Lü, Beijing Cancer Hospital and Institute, Beijing, China), anti-MMP2 (MAB13405, Millipore, Billerica, MA), and ␤-actin antibody (A5316, Sigma).…”
Section: Methodsmentioning
confidence: 99%